SHOWCASING THE DIRECTIVE ILLOCUTIONARY ACT FOUND IN THE MOVIE MISS PEREGRINE'S HOME FOR PECULIAR CHILDREN - Wayan Maystana Setianda; Putu Desi Anggerina Hikmaharyanti (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study examines the concept of illocutionary force in John Searles' speech act theory, with a particular focus on the directive aspect of illocutionary acts. The research seeks to completely examine directive illocutionary actions in the film's language using the film "Miss Peregrine's Home for Peculiar Children (Burton, 2016)" as the data source. Instances of directed illocutionary acts are recorded using targeted sampling, repeated viewings, meticulous observations, and note-taking. Using Searle's theory, a descriptive qualitative analysis categorizes and interprets the evidence. The results show that among the five investigated directed speech actions, questions are the most often (40%), followed by command, request, and prohibition (20% each). This work advances knowledge of speech acts in communication and media art by contributing to a thorough understanding of directed illocutionary actions in the cinema environment. It gives insights into communication dynamics by throwing light on the prevalence and categorization of directed speech actions. The findings of the study, as provided in tables, narrative descriptions, and illustrative examples, emphasize the importance of inquiries and other directing speech actions in both verbal and nonverbal communication. The ramifications of this work extend to a larger knowledge of speech actions, expanding our understanding of communication in many circumstances.